HLA‐DR/DQ molecular mismatch: A prognostic biomarker for primary alloimmunity. Issue 6 (15th December 2018) - Wiebe, Chris; Kosmoliaptsis, Vasilis; Pochinco, Denise; Gibson, Ian W.; Ho, Julie; Birk, Patricia E.; Goldberg, Aviva; Karpinski, Martin; Shaw, Jamie; Rush, David N.; Nickerson, Peter W.
Abstract : Alloimmune risk stratification in renal transplantation has lacked the necessary prognostic biomarkers to personalize recipient care or optimize clinical trials. HLA molecular mismatch improves precision compared to traditional antigen mismatch but has not been studied in detail at the individual molecule level. This study evaluated 664 renal transplant recipients and correlated HLA‐DR/DQ single molecule eplet mismatch with serologic, histologic, and clinical outcomes. Compared to traditional HLA‐DR/DQ whole antigen mismatch, HLA‐DR/DQ single molecule eplet mismatch improved the correlation with de novo donor‐specific antibody development (area under the curve 0.54 vs 0.84) and allowed recipients to be stratified into low, intermediate, and high alloimmune risk categories. These risk categories were significantly correlated with primary alloimmune events including Banff ≥1A T cell–mediated rejection ( P  = .0006), HLA‐DR/DQ de novo donor‐specific antibody development ( P  < .0001), antibody‐mediated rejection ( P  < .0001), as well as all‐cause graft loss ( P  = .0012) and each of these correlations persisted in multivariate models. Thus, HLA‐DR/DQ single molecule eplet mismatch may represent a precise, reproducible, and widely available prognostic biomarker that can be applied to tailor immunosuppression or design clinical trials based on individual patient risk. Abstract : Primary alloimmune risk precisely determined using HLA class II molecular mismatch may facilitate personalized treatment and monitoring strategies for kidney transplant recipients.